Flower-like nickel oxide micro/nanostructures: synthesis and enhanced electrochromic properties. Issue 48 (28th May 2015) - Zhao, Congcong; Du, Fanglin; Wang, Jinmin
<x xml:space="preserve">Abstract</x> NiO micro/nanoflowers synthesized by hydrothermal treatment followed by calcination exhibit enhanced electrochromic properties.